Proton currents constrain structural models of voltage sensor activation - Aaron L Randolph; Younes Mokrab; Ashley L Bennett; Mark SP Sansom; Ian Scott Ramsey (eLife, 2016)
The Hv1 proton channel is evidently unique among voltage sensor domain proteins in mediating an intrinsic ‘aqueous’ H+ conductance (GAQ). Mutation of a highly conserved ‘gating charge’ residue in the S4 helix (R1H) confers a resting-state H+ ‘shuttle’ conductance (GSH) in VGCs and Ci VSP, and we now report that R1H is sufficient to reconstitute GSH in Hv1 without abrogating GAQ. Second-site mutations in S3 (D185A/H) and S4 (N4R) experimentally separate GSH and GAQ gating, which report thermodynamically distinct initial and final steps, respectively, in the Hv1 activation pathway. The effects of Hv1 mutations on GSH and GAQ are used to constrain the positions of key side chains in resting- and activated-state VS model structures, providing new insights into the structural basis of VS activation and H+ transfer mechanisms in Hv1.